Record high external quantum efficiency of 19.2% achieved in light-emitting diodes of colloidal quantum wells enabled by hot-injection shell growth - Liu, Baiquan (2020)
Colloidal quantum wells (CQWs) are regarded as a highly promising class of optoelectronic materials, thanks to their unique excitonic characteristics of high extinction coefficients and ultranarrow emission bandwidths. Although the exploration of CQWs in light-emitting diodes (LEDs) is impressive, the performance of CQW-LEDs lags far behind other types of soft-material LEDs (e.g., organic LEDs, colloidal-quantum-dot LEDs, and perovskite LEDs). Herein, high-efficiency CQW-LEDs reaching close to the theoretical limit are reported. A key factor for this high performance is the exploitation of hot-injection shell (HIS) growth of CQWs, which enables a near-unity photoluminescence quantum yield (PLQY), reduces nonradiative channels, ensures smooth films, and enhances the stability. Remarkably, the PLQY remains 95% in solution and 87% in film despite rigorous cleaning. Through systematically understanding their shape-, composition-, and device-engineering, the CQW-LEDs using CdSe/Cd0.25 Zn0.75 S core/HIS CQWs exhibit a maximum external quantum efficiency of 19.2%. Additionally, a high luminance of 23 490 cd m-2 , extremely saturated red color with the Commission Internationale de L'Eclairage (CIE) coordinates of (0.715, 0.283), and stable emission are obtained. The findings indicate that HIS-grown CQWs enable high-performance solution-processed LEDs, which may pave the path for future CQW-based display and lighting technologies.